Ta-Nb MINERALIZATION IN RARE-METAL PEGMATITES OF THE WORLD AND UKRAINIAN SHIELD - Hrinchenko, O.; Bondarenko, S.; Sydorchuk, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Features of formation of Ta-Nb mineralization in rare-metal pegmatites of the world and Ukrainian Shield are considered. Rare-metal pegmatites of the world with Ta-Nb mineralization are characterised by large variety of mineralogical and geochemical features, internal structure and petrogenesis. At the same time it has been established that typical ore mineral associations of rare-metal pegmatites and Nb/Ta ratio in ores indicate certain type of granitoids on which they are formed – granites of S, І and A type. Among rare-metal pegmatites two families are distinguished. LCT-family pegmatites, which are characterised by enrichment on lithium, caesium and tantalum (Nb/Ta = 0,2-2), are formed mainly after n "sedimentogenic" granitoids of S-type. NYF-family pegmatites, which are characterised by enrichment in niobium (Nb/Ta = 5-10), yttrium and fluorine, are mainly аssociate with anorogenic A-type granitoids. It is considered, that presence of fluxing components (B, P, F) in parental sources of S-type and A-type granites (unlike I-type granites) make them to be the most favorable for formation of pegmatitic melts. As to metallogenic aspect two different provinces – Volynsk (Volynsk megablock) and Central (Ingul megablock) – of distributions of rare-metal granites and pegmatites can be distinguishe in western part of the Ukrainian Shield. In the Volynsk megablock of concentration of rare metals have been established in metasomatically altered alkaline granites of Poessky orogenic belt, in which limits I-type granites (осницкий a complex) and Atype (пержанский a complex) are distributed. Typomorphic features of columbites are represented by values of Ta/Nb ratio which ranges from 1/10 to 1/15 and Fe/Mn one which reaches 1/10 as well as low contents of admixture elements in composition of tantalum-niobates. The Central province of granites and associateв rare-metal pegmatites is characterised by predominant distribution of granitic formations of S-type (Kirovograd complex). Values of Ta/Nb ratio in rare-metal ore manifestations confined to S-type granites range within 1-1,5. Mineralogical and chemical composion of titanium-tantalum-niobates is complex enough – within one mineral aggregate phases with wide range of Ta and Nb are established. Columbite-tantalites are characterised by predominance of ferruginous varieties (Fe/Mn = 2,80-6,56) and high contens of admixture elements. Typomorphic features of tantalum-niobates can be used for establishing possible relations between manifestations of rare-metal mineralization ad genetic types of parental granites.
Keywords: Granites; pegmatites; Ta-Nb mineralization